2008
DOI: 10.1108/02683940810869024
|View full text |Cite
|
Sign up to set email alerts
|

New measures of stereotypical beliefs about older workers' ability and desire for development

Abstract: Purpose – The purpose of this paper is to introduce new measures of stereotypical beliefs about older workers' ability and desire for learning and development and test relationships with key antecedents and outcomes. Design/methodology/approach – In a sample of workers over 40 years of age from across the US workforce, a two‐wave survey study was unique in that it examined stereotypes held by aging workers themselves in relation to their own behavior. Findings – The psychometric qualities of the scales were po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
0
8

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(85 citation statements)
references
References 46 publications
3
69
0
8
Order By: Relevance
“…First, as reported by previous studies (Chiu et al, 2001;Maurer et al, 2008;Posthuma and Campion, 2009), our findings confirm that the stereotypes toward older workers are both positive and negative.…”
Section: Theoretical Implicationssupporting
confidence: 79%
See 2 more Smart Citations
“…First, as reported by previous studies (Chiu et al, 2001;Maurer et al, 2008;Posthuma and Campion, 2009), our findings confirm that the stereotypes toward older workers are both positive and negative.…”
Section: Theoretical Implicationssupporting
confidence: 79%
“…Studying the older workers' self-efficacy for development and improvement of career-relevant skills, Maurer (2001) suggested that the stereotypical representation of older workers as less receptive to new ideas, less capable of learning and less adaptable than younger workers may affect the older employees' self-efficacy for development. This assumption was confirmed by Maurer et al (2008), who found that stereotypical STEREOTYPES TOWARD OLDER WORKERS beliefs about older workers' ability to develop were related to the senior employees' self-efficacy for development.…”
Section: Stereotypes Toward Older Workerssupporting
confidence: 68%
See 1 more Smart Citation
“…Firstly, our findings stress the need for awareness campaigns that will demonstrate the impact of age norms in employment process. Research has shown that executives agree that older workers are discriminated against but they did not believe that this occurred in their own organisations (Maurer et al, 2007). Secondly, training of recruiters towards more age awareness in selection procedures is necessary and can, in the long run, benefit both organisations and older workers by selecting better candidates and create diversity in teams.…”
Section: Discussionmentioning
confidence: 99%
“…Powszechnym stereotypem jest np. przekonanie, że starsi pracownicy są mniej zainteresowani rozwojem własnej kariery i niechętnie uczestniczą w szkoleniach (Maurer, Barbeite, Weiss, Lippstreu, 2008). Stereotyp ten wynika z przekonania, że starsi pracownicy mają obniżoną zdolność przyswajania nowego materiału i trudniej jest się im uczyć (Fritzsche, DeRouin, Salas, 2009).…”
unclassified